2018
DOI: 10.1038/s41598-018-24830-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel analysis of the Harderian gland transcriptome response to Newcastle disease virus in two inbred chicken lines

Abstract: Behind each eye of the chicken resides a unique lymph tissue, the Harderian gland, for which RNA sequencing (RNA-seq) analysis is novel. We characterized the response of this tissue to Newcastle disease virus (NDV) in two inbred lines with different susceptibility to NDV across three time points. Three-week-old relatively resistant (Fayoumi) and relatively susceptible (Leghorn) birds were inoculated with a high-titered (107EID50) La Sota strain of NDV via an oculonasal route. At 2, 6, and 10 days post infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 27 publications
1
50
0
Order By: Relevance
“…Because the transcriptome is not stagnant, a more comprehensive physiological picture can be obtained by an integrative analysis of the transcriptomes of multiple tissues at multiple time points after a treatment. Previously, the trachea epithelial cells, lung, and Harderian gland of Fayoumis and Leghorns at 2, 6, and 10 days post-infection (dpi) with lentogenic NDV have been individually analyzed with RNA-seq (Deist et al, 2017a;Deist et al, 2017b;Deist et al, 2018). The three tissues had very distinct responses to NDV (Deist et al, 2017a;Deist et al, 2017b;Deist et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the transcriptome is not stagnant, a more comprehensive physiological picture can be obtained by an integrative analysis of the transcriptomes of multiple tissues at multiple time points after a treatment. Previously, the trachea epithelial cells, lung, and Harderian gland of Fayoumis and Leghorns at 2, 6, and 10 days post-infection (dpi) with lentogenic NDV have been individually analyzed with RNA-seq (Deist et al, 2017a;Deist et al, 2017b;Deist et al, 2018). The three tissues had very distinct responses to NDV (Deist et al, 2017a;Deist et al, 2017b;Deist et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the trachea epithelial cells, lung, and Harderian gland of Fayoumis and Leghorns at 2, 6, and 10 days post-infection (dpi) with lentogenic NDV have been individually analyzed with RNA-seq (Deist et al, 2017a;Deist et al, 2017b;Deist et al, 2018). The three tissues had very distinct responses to NDV (Deist et al, 2017a;Deist et al, 2017b;Deist et al, 2018). Taking a systems biology approach and analyzing the three tissues together will provide a more comprehensive picture of how the whole animal responded to NDV.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, the observed time effect on the expression of IFNB may help to explain the different rates of viral clearance between lines, as the Fayoumi had lower viral load than the Leghorn at 6 dpi 19,20 . Recognition of viral RNA by TLR7 triggers signaling for cytokines with antiviral activity to be upregulated 29 .…”
Section: Discussionmentioning
confidence: 74%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ (Ghs6 and Ghs13), have shown that the Major Histocompatibility Complex (MHC) can contribute to the genetic resistance against NDV 28 . Evaluation of the transcriptome of these two genetically distinct lines also suggests that NDV infection may cause upregulation of different genes in a line-dependent manner 19 . These results were also observed in the spleen, where few interferon stimulated genes were upregulated by NDV challenge 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation